COMPARISON OF 10% BUFFERED FORMALIN NEUTRAL FIXATION SOLUTION WITH BOUIN ON MICROSCOPIC IMAGES OF CHICKEN HEPAR AND CEREBRUM WITH HEMATOXYLIN EOSIN (HE) STAINING - Sitanggang, Robestri Natalia (Jurnal Biosains Pascasarjana, 2025)
The fixation process is an important stage in the manufacture of histopathology preparations. Fixation aims to prevent autolysis and tissue degradation, so that the results can be observed both anatomically and microscopically. Fixation solutions that are often used in routine histopathological examinations are 10% Formalin Buffer Neutral and Bouin. This study was used to determine the results of the comparison of 10% NBF fixation solution with Bouin on the microscopic picture of hepar and cerebrum with hematoxylin eosin staining. The type of research used is a cross sectional approach with a qualitative descriptive design. Sampling was performed on chicken animals. The samples used were hepar and cerebrum fixed with 10% NBF and 10% Bouin for 12 hours, stained with Hematoxylin Eosin and observed microscopically. Then give an assessment with good, less good, or not good categories based on assessment indicators based on cell color and shape. The results showed a microscopic picture of hepatic and cerebrum tissue as much as 6 preparations fixed with 10% NBF liquid showed good results. While hepatic and cerebrum tissue fixed with bouin liquid as many as 6 preparations showed poor results. The conclusion is that there are differences in the microscopic results of hepatic and cerebrum tissue fixed with 10% NBF solution and Bouin. Good microscopic observation results based on the assessment indicator criteria are tissues fixed with 10% NBF liquid.